Issues of Grammar and the Forms of Quranic Grammar in (Al-Mujam Al-Waseet) and Their Effect on Giving the Meaning - Omer, Abo Haneefa Omer Alshareef Ali; Soliman, Mohamed Fawzy Fotouh; Alquhtani, Mohammed Abdullah Al Mazah (Journal of Humanities & Social Sciences, 2021)
The research deals with the issues of grammar in (Al-Mujam Al-Waseet) through its terminologies, the forms of Quranic grammar, and the effect of that on giving the linguistic meaning. One of the objectives to be achieved is: To study the grammatical terms contained in (Al-Mujam Al-Waseet) and connect them to the theory of Quranic grammar, and to identify how to prove the grammatical rule out of the Quranic evidence in (Al-Mujam Al-Waseet). The major terms in the two sections were handled. The importance of the research lies in presenting a grammatical issue in a lexical dictionary besides linking it to what was mentioned in the grammar books. Because of the nature of the research, the descriptive and analytical approach was followed, the nature of the study required that it should be on two parts, as arranged in (Al-Mujam Al-Waseet) “nouns and verbs”. The main terms in the two sections were discussed. A conclusion has been appended to the grammatical issues in which the results of the scientific paper were explained.